Association between urodynamic parameters and urine neutrophil gelatinase–associated lipocalin concentrations in children with neuropathic bladders. Issue 2 (April 2019) - Forster, C.S.; Goldstein, S.; Pohl, H.; Jackson, E.
Summary: Background: Neutrophil gelatinase–associated lipocalin (NGAL) is a marker of acute kidney injury, and has been shown to be a sensitive marker of renal damage in urinary tract obstruction. Children with neurogenic bladders are at risk of renal damage as a result of increased pressure within the urinary system. A marker of upper tract deterioration in this population would be useful to guide management. Objective: The aim of the study is to compare urinary NGAL (uNGAL) concentrations between children who have elevated and normal detrusor pressure and between those with low and normal compliance, on urodynamics. Study design: This is a cross-sectional study of children with neurogenic bladder who underwent routine urodynamics from August 2015 to March 2016. Patients with positive urine cultures from the time of urodynamics were excluded from analysis. Urine was obtained from the time of urodynamics for uNGAL measurement. Urodynamics were reviewed. High pressure is defined as a detrusor pressure of 40 cm of water or greater at the volume where catheterization is normally performed. Compliance was calculated at the volume where catheterization is performed. Results: A total of 89 patients were included (low pressure, n = 73; high pressure, n = 16 and low compliance, n = 41; normal compliance, n = 40). Median uNGAL concentrations were not different between patients with low and high pressure, but there was a higher median uNGAL concentration in patients with normal compliance compared with those with low compliance. There was no correlation between maximum detrusor pressure and uNGAL concentration, but there was a moderate relationship between compliance and uNGAL concentration (rs = 0.43, p < 0.01 for non-normalized uNGAL and rs = 0.30, p < 0.01 for normalized uNGAL). Discussion and conclusion: There is an increase in uNGAL concentrations in patients with normal compliance compared with those with low compliance, but no difference between patients with low or high pressure. Summary Figure Urinary NGAL concentrations in patients with low vs high detrusor pressure and those with low vs normal compliance. Urinary NGAL concentrations are significantly elevated in patients with normal compliance compared with those with low compliance, but there is no difference between patients with low and high pressure. NGAL, neutrophil gelatinase–associated lipocalin. Summary Figure